Color stability of a composite resin modified by ZnO and TiO2 antibacterial nanoparticles - Dias, Hercules Bezerra; Sicilia, Lucca; Bernardi, Maria Ines Basso; Hernandes, Antônio Carlos; Rastelli, Alessandra Nara de Souza (Brazilian Dental Science, 2026)
Objective: To evaluate the color stability of a composite resin modified with ZnO and TiO2 nanoparticles (both pure and silver decorated), synthesized via polymeric precursor and hydrothermal methods. Material and Methods: Filtek™ Z350 XT resin was modified with 2 wt% of nanoparticles, specimens were prepared (n=180), and photoactivated. Specimens were immersed in coffee and artificial saliva; color changes were measured spectrophotometrically, converted to NBS units, and analyzed using repeated measures ANOVA (p